A comparison of the test-negative and the matched case-control study designs for estimation of EV71 vaccine immunological surrogate endpoints from a randomized controlled trial - Li Zhang; Pengfei Jin; Mingwei Wei; Hudachuan Jiang; Jingxin Li; Fengcai Zhu (Human Vaccines & Immunotherapeutics, 2022)
Since TND could be an appropriate method to assess vaccine effectiveness, we want to know whether it may be used for the estimation of vaccine immunological surrogate endpoints, like case-control study. We conducted two study designs (test-negative design (TND) VS matched case-control design (MCC)) to evaluate immunological surrogate endpoint against EV71-associated diseases. We calculated sensitivity (proportion of participants with EV71-associated disease who have a titer less than the cutoff at day 56), specificity (proportion of matched controls who have a titer equal or greater than the cutoff at day 56), and corresponding Youden index ([sensitivity + specificity] − 1). Then, we compared them between TND and MCC. In test-negative design, we totally enrolled 7029 subjects, 49 tested positive as cases and 6980 tested negative as controls in per-protocol population. In matched case-control design, we totally enrolled 305 subjects, 51 as cases, and 254 as controls in whole cohort. In sensitivity and specificity comparison, TND and MCC’s results were similar to each other, except for a titer of 1:4. Nonetheless, in Youden index comparison, MCC’s results were slightly higher than the TND’s, except for a titer of 1:4. EV71 vaccine immunological surrogate endpoints derived from TND was similar to MCC’s. Our results supported that TND could become an alternative research design with the progress of surveillance.